Clinical cardiogenetics - Baars, H. F. (Springer, 2011)
Clinical management and signs are the focus of this practical cardiogenetic reference for those who are involved in the care for cardiac patients with a genetic disease. With detailed discussion of the basic science of cardiogenetics in order to assist in the clinical understanding of the topic. The genetic causes of various cardiovascular diseases are explained in a concise clinical way that reinforces the current management doctrine in a practical manner. The authors will cover the principles of molecular genetics in general but also specific to cardiac diseases. They will discuss the etiolo.